Design a Strategic Program to Strengthen Beef Cattle Corporate Institutions - Rohani, ST; Siregar, Ahmad Ramadhan; Rasyid, Tanrigiling; Hatta, Muhammad; Diansari, Pipi; Astaman, Putra; Darwis, Muhammad; Kurniawan, Muhammad Erik; Utama, A. Della Riski (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2024)
The development of beef cattle operations is conducted cohesively and sustainably within the livestock industry, considering socio-cultural, technical, economic, and ecological factors. It also fosters investment, business expansion, and job creation, and improves farmers' welfare. This research aims to design a strategic program to strengthen corporate institutions for beef cattle at the D'Reppa Cow House, Gowa Regency. This research used a survey method with interviews. Primary data was obtained through interviews with informants/experts using questionnaires and analyzed using Interpretative Structural Modeling (ISM) to formulate complexity, hierarchy (levels), and classification between elements. The results of this research show that the ten sub-elements of the strategic program for strengthening beef cattle livestock corporations at the D'Reppa Cow House, Gowa Regency, are divided into four quadrants. The strategic program design for the institutional strengthening of beef cattle livestock corporations is establishing a research and development base camp for beef cattle farming businesses based on livestock corporations. The research has limitations in terms of data collection constrained to informants difficult to find so data collection is not optimal, in addition, farmers still do not know about massive livestock corporations. Future research is expected to pay attention to the shortcomings of this study in the aspect of data collection and determining responses